Productivity improvement in a manufacturing company using Poka-Yoke [compact disc] - 355786 Cheng, Wee Jian (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2006